EPA guidance on treatment of negative symptoms in schizophrenia. Issue 1 (17th March 2021) - Galderisi, S.; Kaiser, S.; Bitter, I.; Nordentoft, M.; Mucci, A.; Sabé, M.; Giordano, G. M.; Nielsen, M. Ø.; Glenthøj, L. B.; Pezzella, P.; Falkai, P.; Dollfus, S.; et al.
Abstract: Negative symptoms of schizophrenia remain a major therapeutic challenge. The progress in the conceptualization and assessment is not yet fully reflected by treatment research. Nevertheless, there is a growing evidence base regarding the effects of biological and psychosocial interventions on negative symptoms. The importance of the distinction between primary and secondary negative symptoms for treatment selection might seem evident, but the currently available evidence remains limited. Good clinical practice is recommended for the treatment of secondary negative symptoms. Antipsychotic treatment should be optimized to avoid secondary negative symptoms due to side effects and due to positive symptoms. For most available interventions, further evidence is needed to formulate sound recommendations for primary, persistent, or predominant negative symptoms. However, based on currently available evidence recommendations for the treatment of undifferentiated negative symptoms (including both primary and secondary negative symptoms) are provided. Although it has proven difficult to formulate an evidence-based recommendation for the choice of an antipsychotic, a switch to a second-generation antipsychotic should be considered for patients who are treated with a first-generation antipsychotic. Antidepressant add-on to antipsychotic treatment is an option. Social skills training is recommended as well as cognitive remediation for patients who also show cognitive impairment. Exercise interventions also have shown promise. Finally, access to treatment and to psychosocial rehabilitation should be ensured for patients with negative symptoms. Overall, there is definitive progress in the field, but further research is clearly needed to develop specific treatments for negative symptoms.